Distinct mitochondrial HSP70 homologues conserved in various Leishmania species suggest novel biological functions - Campos, Rodrigo M.; Nascimento, Mirna; Candido Ferraz, J.; Pereira, Mariana M. C.; Rocha, Pollyanna O.; Thompson, Gloria M. [UNESP]; Cysne-Finkelstein, Lea; Figueiredo, Regina C. B. Q.; de Melo Neto, Osvaldo P. (Elsevier B.V., 2008)
We report the identification of two distinct homologues of the 70-kDa mitochondrial heat shock protein (mtHSP70) from Leishmania chagasi/Leishmania infantum (Lc2.1 and Lc2.2). in Leishmania species, multiple genes encoding Lc2.2 are present whilst single genes encode Lc2.1. Strikingly, genes encoding Lc2.1-like proteins are absent from Trypanosoma species. Lc2.2 is characterized by a poly-glutamine rich C-terminus, absent from Lc2.1 or mtHSP70 homologues outside the trypanosomatids. Lc2.1 displays unique substitutions within its peptide-binding domain which modify amino acids strictly conserved in cytoplasmic and mitochondrial HSP70 proteins alike. Affinity purified antibodies recognize mainly a single protein in extracts from promastigotes/epimastigotes of various Leishmania/Trypanosoma species. Upon differentiation of Leishmania amazonensis into amastigotes a second protein (presumably Lc2.1) is induced and becomes the predominant mtHSP70 homologue expressed. Subcellular localization of these proteins was investigated and ratified a distribution throughout the mitochondrial matrix. Our results imply novel mtHSP70 functions which evolved within the genus Leishmania. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Leishmania chagasi; heat shock proteins; mtHSP70; mitochondria